Induction of recombination between homologous and diverged DNAs by double-strand gaps and breaks and role of mismatch repair. - Priebe, S D (1994)
Sequence homology is expected to influence recombination. To further understand mechanisms of recombination and the impact of reduced homology, we examined recombination during transformation between plasmid-borne DNA flanking a double-strand break (DSB) or gap and its chromosomal homolog. Previous reports have concentrated on spontaneous recombination or initiation by undefined lesions. Sequence divergence of approximately 16% reduced transformation frequencies by at least 10-fold. Gene conversion patterns associated with double-strand gap repair of episomal plasmids or with plasmid integration were analyzed by restriction endonuclease mapping and DNA sequencing. For episomal plasmids carrying homeologous DNA, at least one input end was always preserved beyond 10 bp, whereas for plasmids carrying homologous DNA, both input ends were converted beyond 80 bp in 60% of the transformants. The system allowed the recovery of transformants carrying mixtures of recombinant molecules that might arise if heteroduplex DNA--a presumed recombination intermediate--escapes mismatch repair. Gene conversion involving homologous DNAs frequently involved DNA mismatch repair, directed to a broken strand. A mutation in the PMS1 mismatch repair gene significantly increased the fraction of transformants carrying a mixture of plasmids for homologous DNAs, indicating that PMS1 can participate in DSB-initiated recombination. Since nearly all transformants involving homeologous DNAs carried a single recombinant plasmid in both Pms+ and Pms- strains, stable heteroduplex DNA appears less likely than for homologous DNAs. Regardless of homology, gene conversion does not appear to occur by nucleolytic expansion of a DSB to a gap prior to recombination. The results with homeologous DNAs are consistent with a recombinational repair model that we propose does not require the formation of stable heteroduplex DNA but instead involves other homology-dependent interactions that allow recombination-dependent DNA synthesis.